Análise de estratégias para melhoria do conforto térmico em salas de aulas - Chaves, Victor Leandro Arantes (2016)
The unsatisfactory thermal performance of buildings belonging to higher education institutions in Brazil cause users discomfort in classrooms and affect student performance. To ensure the well- being to the user, the use of mechanical systems for cooling of environments such as the use of air conditioners is necessary to reduce air temperature indoor, by one hand, and increase the energy expenditure of the building by about 50%, by the other side. This study analyses thermal comfort and energy efficiency in the School of Civil Engineering and Environmental UFG through measurements "in loco" and the perception of the users as well as by computer simulation. The methodology consists of: a) analysis of architectural design; b) lifting climatic summer data on air temperature and humidity within the classroom, and the views of users in three different situations - with open windows and doors and on evaporative air conditioner, open windows and doors and natural ventilation, and windows and doors closed and air conditioning on -; c) treatment of climatic data; d) comparison of the collected results and the perception of the users; e) evaluation thermal energy by computer simulation and prescriptive method of RTQ-C. They interviewed 200 users. About 83.3% of respondents were dissatisfied in the situation with natural ventilation, 68.5% in the situation on evaporative air conditioner and 70.2% in the situation with air conditioning on. Although the results suggest that the situation using air conditioners is the most comfortable, the number of users who feel uncomfortable is very high in all situations, not meeting the levels recommended by the ISO 7730 (2005).